Poems Collection Structures of "HANJAREY ZAKHMI TAGHAZOL (The Sore Larynx Lyricism)" of Hussein Monzavi - زیور دهقانی; شمس الحاجیه اردلانی; سید احمد کازرونی (مطالعات زبانی و بلاغی)
Repetition and circle are the main axes of the formation of musical elements. This pattern is also found in the musical system of modern poetry and covers three inner, outer and aside music areas. Based on these patterns, Monzavi has created the music of his poems. This study aims to examine the music creator arrays in sonnets of the collection "HANJAREY ZAKHMI TAGHAZOL" (sore throat lyricism) and the method of using these elements and also their function in Monzavi poems has been shown. The findings of this research suggest that Monzavi use different ways for the musical richness of his own lyrics including: paying attention to the diversity of prosodic rhythms, employing useful rhythms, create proper meaning and thematic with the rhythm of prosody, pun utilizing, repetition, contrast, rhymes musical function that make his poems unison, totally, Monzavi poem musicality elements classified in four categories: Outer music, aside music, internal music and spiritual music.